Strengthening Student Digital Literature Capacity in Implementation of E-Learning in the Covid-19 Pandemic (Study in Social Welfare Study Program, Faculty of Social and Political Sciences, Bengkulu University) - Alex Abdu Chalik; Fransiska Timoria Samosir (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research objectives to be achieved in this study are to get an overview and explanation of strengthening the digital literacy capacity of students in implementing e-learning during the Covid-19 pandemic. This research method uses a qualitative descriptive method combined with a frequency table. Data was collected through in-depth interview techniques, observation and documentation study. In-depth interviews were conducted with students using the WhatsApp application and face to face. Documentation is done by collecting secondary data that is owned by the website of the Department of Social Welfare Science, Faculty of Social and Political Sciences, UNIB. The results revealed that the average personality of the lecturers and students consisted of financial ability, ownership of internet networks,simplicity which consists of the ability of the lecturer to provide reading material that can be understood, the ability to make / read teaching aids (PPT) that can be understood, and the ability to use language that is easy to understand is owned by the lecturer well, speed which consists of ownershiinternet access, the speed at which the lecturer provides lecture material, the ability of the lecturer to provide material quickly, the ability of the lecturer to provide course material that can be read quickly and the ability of the lecturer to evaluate the ability of students to receive course material can run well.